Delivering normative feedback to heavy drinking college students via text messaging: A pilot feasibility study. (August 2018) - Merrill, Jennifer E.; Boyle, Holly K.; Barnett, Nancy P.; Carey, Kate B.
Abstract: Correcting misperceptions in drinking norms is an established method of reducing college student drinking; however, delivery of accurate norms has typically been limited to a single dose within the confines of an alcohol intervention. The present study tests the feasibility, acceptability, and preliminary efficacy of using text messages to promote pro-moderation descriptive and injunctive norms. Following a baseline survey, 68 heavy drinking college students were randomly assigned to receive 28 daily messages with either accurate norms information (experimental group, n = 34) or fun facts (control group, n = 34). Participants rated each message on a 5-point scale of interest, and at the end of the 28 days completed a follow-up assessment of normative perceptions and drinking behavior. The study protocol was feasible: 87% of invited students completed the screener, 64% of eligible students completed the consent form, and 93% agreed to participate. All messages were delivered and 98% were rated. Regarding acceptability, the mean interest rating for the alcohol-related text messages was 2.84 ( SD = 1.30), and no participants withdrew from the study. Although between-group differences were not observed at follow-up, participants in the experimental group showed significant reductions between baseline and follow-up on peak drinks, frequency of heavy episodic drinking (HED), negative consequences, and injunctive norms ( p s < 0.01). Results lay the groundwork for development of a text-based prevention strategy for use in college settings. Highlights: Accurate descriptive, injunctive norms sent to college students in 28 daily texts. Demonstrated feasibility and acceptability of using text messages to target norms. Participants in experimental group reduced drinking behavior at post-test.